KEBAHAGIAAN ANAK DIDIK PEMASYARAKATAN (ANDIKPAS) DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II AMBON - Natinggel Novalina Sovia Wermasubun; Sri Aryanti Kristianingsih (Bajang Institute, 2023)
Happiness is a life satisfaction that everyone wants to experience. The purpose of this research is to find out the description of happiness and the factors that influence the happiness of correctional students (andikpas). The data in this study were obtained using a qualitative method with a case study type. Respondents in this study were male correctional students (andikpas) aged 16-18 years who had committed crimes. Collection of research data by means of interviews. The results showed that the three participants had different factors for their happiness.